PERAN MEDIASI MINAT BELI PADA PENGARUH CELEBRITY ENDORSER DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN (MOTIVASI, 2023)
Purpose– This research aims to determine and analyze the influence of celebrity endorsers and social media marketing on purchasing decisions for Azarine skincare with purchase interest as an intervening variable. Design/methodology– The method used in this research is using a type of approach quantitative descriptive. The population in this study were students from the Management Study Program Faculty of Economics and Business, Universitas Muhammadiyah Sumatra Utara totaling 431 people, while the sampling method using the Slovin formula, so that a sample of 100 is obtained person. Data collection methods using questionnaires and documentation studies Meanwhile, the data analysis technique uses the Path Analysis Model Statistics namely Partial Least Square-Structural Equation Model (PLSSEM) using the SmartPLS 3 application. Findings - The research results show that celebrity endorsers and social media marketing Instagram have a significant effect on purchasing interest. Instagram social media marketing has a significant influence on purchasing decisions, but celebrity endorsers have no influence on purchasing decisions. Furthermore, buying interest has no influence on purchasing decisions, thus meaning that buying interest is not able to act as a mediator